Paraguay : Fourth Review Under the Stand-By Arrangement and Request for Waiver of Performance Criteria. (IMF Staff Country Reports; Country Report ;, 2006)
Paraguay's Fourth Review Under the Stand-By Arrangement and Request for Waiver of Performance Criteria are examined. The main challenge is to consolidate the macroeconomic gains achieved thus far and deepen structural reform. A stable macroeconomic environment will be the key for creating the conditions for sustainable growth and poverty reduction. Although all areas of structural reform are important, public banking reform has proved to be difficult, and its implementation will signal the resolve of the authorities to carry on with the reform agenda.